2012
DOI: 10.1063/1.3686233
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine particle size distribution during high velocity impact of high density metals

Abstract: Luminescence induced by high-velocity impacts of metallic particles on metal surfacesAbstract. In the event of high-energy penetrator impact, people involved in battlefield scenarios are exposed to the additional hazard stemming from ultrafine metallic particles, i.e. exposure, inhalation, and respiration of aerolized metals. In order to have reliable quantitative measurement of the aerosol particles generated under controlled impact conditions, an experimental set-up was designed to perform impact tests with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Time change and size distributions of UFP count following ammunition-blasting operations were similar to those observed during high-speed impact of inert bombs; some differences in the peak readings were related to the variable distances of the stationary sampler from the detonation box [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Time change and size distributions of UFP count following ammunition-blasting operations were similar to those observed during high-speed impact of inert bombs; some differences in the peak readings were related to the variable distances of the stationary sampler from the detonation box [ 20 , 22 ].…”
Section: Discussionmentioning
confidence: 84%
“…Instead, in inert bomb launches, we expected generation of particles in the large size range, because of the mechanical impact of the inert to the ground from high altitude. However, previous studies suggested a potential UFP production during high-speed mechanical impacts [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano magnesium particle is also a promising material for cancer therapeutics in biomedical science. While any changes to the particle size distribution (PSD) can affect the size-determined nano-properties or potential nanoproperties to a great extent, this leads to the fact that the application fields vary with each PSD [15][16][17][18][19]. Hence, the master of each PSD formation conditions is of prime importance.…”
Section: Introductionmentioning
confidence: 98%
“…RoR experiment was performed to avoid friction forces along the impact surface during impact, in order to integrate data already obtained with classic Taylor impact test against anvil [17,18]. a barrel (3500 mm long) in which the projectile is accelerated by the expanding fluid, and an impact chamber (2.5 m 3 ) where the impact occurs and the measurements are performed.…”
Section: Rod-on-rod Test: Materials and Methodsmentioning
confidence: 99%